Spectrophotometric Study of Ternary Complex Forming Systems of Some Lanthanide Metal Ions with Eriochrome Cyanine R in Presence of Cetylpyridinium Bromide for Microdetermination - A. S. Dhepe; A. B. Zade (E-Journal of Chemistry)
Study of coordination compounds of lanthanide elements has received a great attention due to growing applications in science and technology. Number of chromogenic reagents form water soluble colored complexes with lanthanides. Eriochrome cyanine R (ECR) a member of triphenylmethane type of dye has been reported to form green colored complexes with lanthanides and has been used for microdetermination of these metal ions. Addition of cationic surfactant, Cetylpyridinium bromide (CPB), a cationic surfactant sensitizes the color reactions of Gd(III), Tb(III), Dy(III), Ho(III) and Lu(III) with ECR. Formation of water soluble, highly colored ternary complexes with a considerable bathochromic shift of about 50 nm in presence of surfactant has been observed. Optimum reaction conditions and other analytical parameters were also evaluated. Stoichiometric ratio 1:3:3 of Ln: ECR: CPB are responsible for the observed rise in molar absorptivity and sensitivity. Beer’s law was obeyed between 0.50 to 13.00 ppm. Effective photometric range and molar absorptivity of these ternary complexes have been calculated. Effect of some common interfering ions on determination of these lanthanide metal ions was studied. A simple, rapid and highly sensitive spectrophotometeric method has been proposed for the determination of metal ions understudy.